2022
DOI: 10.18585/inabj.v14i2.1800
|View full text |Cite
|
Sign up to set email alerts
|

Parkia speciosa Seeds Ethanol Extract as Co-chemotherapeutic Agent for Doxorubicin Toward Tongue Cancer

Abstract: BACKGROUND: Parkia speciosa seeds have been reported to have an anticancer property due to the presence of various antioxidant compounds. Since the potential uses of P. speciosa for the tongue cancer has not been clearly disclosed, we conducted a study to investigate anticancer properties of P. speciosa seed ethanol extract (PSSEE) as well as its effect on cardiac cells.METHODS: Tongue cancer rat model were treated with/without Doxorubicin and various concentrations of PSSEE. After treatment, tongue and heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…(10) In addition, natural products may also have an ability as co-chemotherapy agents to enhance the efficacy of other chemotherapy agents. (11) Amongst natural products, caffeic acid (3,4-dihydroxycinnamic acids), which commonly occurs in fruits, tubers, legumes and grains, has been reported to provide protection from various diseases, such as bone resorption (12)(13)(14)(15)(16), diabetic kidney disease (17), Alzeheimer's disease (18) and cancers. (19,20) Studies have shown that caffeic acid triggers MG-63 osteosarcoma cell apoptosis by activating caspases (21,22) and may affect intrinsic and extrinsic apoptotic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…(10) In addition, natural products may also have an ability as co-chemotherapy agents to enhance the efficacy of other chemotherapy agents. (11) Amongst natural products, caffeic acid (3,4-dihydroxycinnamic acids), which commonly occurs in fruits, tubers, legumes and grains, has been reported to provide protection from various diseases, such as bone resorption (12)(13)(14)(15)(16), diabetic kidney disease (17), Alzeheimer's disease (18) and cancers. (19,20) Studies have shown that caffeic acid triggers MG-63 osteosarcoma cell apoptosis by activating caspases (21,22) and may affect intrinsic and extrinsic apoptotic pathways.…”
Section: Introductionmentioning
confidence: 99%